Decomposing school and school-type effciency - Portela, M. C. A. Silva (2011)
This paper puts forward a Data Envelopment Analysis (DEA) approach to decomposing a pupil’s under-attainment at school. Under-attainment is attributed to the pupil, the school and the type of funding regime under which the school operates. A pupil-level analysis is used firstly on a within school and secondly on a between school basis, grouping schools by type such as state-funded, independent and so on. Overall measures of each pupil’s efficiency are thus disentangled into pupil, school and school-type efficiencies. This approach provides schools with a set of efficiency measures, each one conveying different information.